Improving Logical Thinking Skills through Sorting Box Games for 5-6 Years Old Children at Ra Ar Raudhah Ganjuran - Kholifah, Ida; Darniati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve logical thinking skills through sorting box games in children aged 5-6 years at RA Ar Raudhah. Based on the background of the problem, namely the problem in the material of introducing geometric shapes and grouping geometric shapes has not been optimal because the media used is less varied and interesting for children. then a problem can be formulated, namely How to improve logical thinking skills through sorting box games in children aged 5-6 years at RA Ar Raudhah? and Can this sorting box game improve the logical thinking of children aged 5-6 years? This study is a classroom action research with the research subjects being the data of children at RA AR RAUDHAH group B totaling 12 children, consisting of 4 sons and 8 daughters. The purpose of this learning research is